1993
DOI: 10.1177/019372359301700108
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diversity on Campus: a Look At Intercollegiate Football Coaches

Abstract: Those who attempt to increase cultural diversity in social organizations need to consider perceptions of access or opportunity for prestigious and visible positions. This research investigated career option viability for the positions of college athletic director and football coach through the examination of social characteristics of persons holding these positions at a sample of NCAA Division I-A institutions. Eighty-eight of the 105 institutions contacted supplied a copy of their 1990 football media guide. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…Based on this theory and the supporting empirical evidence, we expect that racial minorities, relative to Whites, might expect more barriers and fewer supports for becoming a coach. Indeed, past research supports this reasoning, as coaches of color have been shown to face discrimination in the hiring and selection process (Anderson, 1993; and anticipate that racial discrimination will limit their upward mobility (Cunningham et al, 2006). Further, they receive differential returns on their human and social capital investments , meaning that even when supports are present, minorities are not rewarded for them in the same manner as are Whites.…”
Section: Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Based on this theory and the supporting empirical evidence, we expect that racial minorities, relative to Whites, might expect more barriers and fewer supports for becoming a coach. Indeed, past research supports this reasoning, as coaches of color have been shown to face discrimination in the hiring and selection process (Anderson, 1993; and anticipate that racial discrimination will limit their upward mobility (Cunningham et al, 2006). Further, they receive differential returns on their human and social capital investments , meaning that even when supports are present, minorities are not rewarded for them in the same manner as are Whites.…”
Section: Studymentioning
confidence: 95%
“…Several studies have focused on the coaches themselves, with findings suggesting that racial minorities face barriers in obtaining coaching positions (Cunningham & Sagas, 2005). When they do earn those positions, coaches of color are often placed in peripheral roles (Anderson, 1993) or hired to aid in recruiting minority athletes (Brown, 2002). When on the job, coaches receive fewer returns for their social capital investments (Sagas & Cunningham, 2005), have fewer opportunities for advancement (Cunningham, Bruening, & Straub, 2006), and perceive discrimination based on their race (Cunningham et al, 2006).…”
mentioning
confidence: 99%
“…This net effect of race suggests that race matters beyond Black and White coaches' differential access to and placement in positions that induce or inhibit mobility in predicting subsequent career attainment. If tracking processes were primarily driving racial inequality in the college football coaching profession, as suggested in prior research (see Anderson, 1993), race should only matter in terms of coaches' access to central positions, both as athletes and coaches. By finding persistent effects of race, these results point to Black and White coaches receiving differential mobility returns from occupying the same coaching positions.…”
Section: Differential Access and Promotions To Executive Positionsmentioning
confidence: 83%
“…The risk period for this analysis is the season in which coaches began their first full-time job until (a) they transition to an FBS executive position or (b) they reach the end of the observation period without experiencing the transition-event (i.e., censored). The use of event-history methods offers numerous advantages over cross-sectional methods, such as logistic regression or descriptive crosstabulations, that have been common in prior research examining racial segregation in the coaching profession (e.g., Anderson, 1993;Braddock, Smith, & Dawkins, 2012;Finch et al, 2010). First, they allow for the investigation of coaches' entire career histories to determine if and when they have occupied high-status positions.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…While Staley and Williams represent "success" stories, it is a wonder as to how many other Black female college athletes could transition to work as professionals in intercollegiate athletics if their respective member institutions adopted inclusive excellence practices encompassing a sense of belonging. I make this statement as extant research on the NCAA and its member institutions' racial and gender composition connote the need for a diverse organizational culture, particularly with its hiring practices and representative administrators and coaches (Anderson, 1993;Cunningham & Sagas, 2004;Fink, Pastore, & Reimer, 2001). Based on research and the 2017 college sports report conducted by TIDES, the NCAA remains a transitional organization.…”
Section: Sense Of Belonging In College Sportmentioning
confidence: 99%